Incorporating Cultural Design Elements in Mobile Applications Creative Industries in Malaysia: A Conceptual Study - Muhammad Zulhimi Samsuri; Shamsul Arrieya Ariffin; Nur Saadah Fathil (Pejabat Karang Mengarang UPSI, 2021)
In the creative industries sector, mobile applications are the creative multimedia division for advancing technology, the industry revolution 4.0 (IR 4.0), in developing creative products. The creative industries benefit from the usage of mobile applications since it allows for the digital manufacturing of creative products that meet the IR 4.0 era. However, research on the use of cultural design aspects in mobile applications has several limits. This research aims to talk about the conceptual framework for the research that will be done to tackle the issues that occur. According to preliminary findings, the design concepts analysed a lack of cultural design aspects. Therefore, the researcher will research to generate design guidelines for mobile applications for the creative industries that include cultural design elements.